Review of nutrition guidelines relevant for adolescents in low‐ and middle‐income countries. Issue 1 (April 2017) - Lassi, Zohra S.; Mansoor, Tarab; Salam, Rehana A.; Bhutta, Shereen Z.; Das, Jai K.; Bhutta, Zulfiqar A.
Abstract : The economic and social well‐being of any country will one day depend on its current adolescent population. To provide a good foundation for healthy adolescent development, healthy diet, along with physical activity and adequate nutrients, is necessary. Therefore, addressing the nutrition needs of adolescents could be an important step toward breaking the vicious cycle of intergenerational malnutrition, chronic diseases, and poverty. These problems could be addressed with timely recognition and appropriately delivered interventions. Our aim here is to review the existing guidelines on various aspects of nutrition interventions for adolescents and young women. We review all of the major existing guidelines on adolescent nutrition. We were able to find 18 guideline bodies that covered some form of nutritional advice in guidelines that targeted adolescents. Although the guidelines that focus specifically on this age group are limited in scope, we also extrapolated recommendations from guidelines focused on adults, women of reproductive age, and pregnant women, which were based on evidence that included populations of adolescent girls. We were able to extract and synthesize specific directives for nutrition in adolescents, macro‐ and micronutrient supplementation, exercise, obesity, and nutrition during preconception, pregnancy, and the postconception period.